MENINGKATKAN KEMAMPUAN MENIRU BENTUK MELALUI STRATEGI PEMBELAJARAN GRADASI DENGAN MEDIA PLASTISIN PADA KELOMPOK B DI TK TUNAS BANGSA KERTA BUANA TENGGARONG SEBERANG TAHUN AJARAN 2016/2017 - Rika - Mardiah; Hanita Hanita; Farny Sutriany Jafar (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
The researcher observed that students in Group B at TK Tunas Bangsa Kerta Buana Tenggarong Seberang had problems in replicating shapes. Therefore, to solve the problem, the researcher conducted a classroom action research, with purpose, to find out whether the implementation of gradation learning strategy by utilizing plasticine as the media of learning is able to enhance students’ ability in making shape replication. Moreover, the researcher involved 12 students; 7 males and 5 females, as the research subjects. To collect the data, the researcher employed observation and documentation technique during two cycles. It is important to note that each cycle consists of planning, implementation, observation and reflection. Meanwhile, for data analysis, the researcher applied percentages. Students’ ability in replicating shapes is measured based on five aspects; 1) ability in replicating the determined shape, 2) tidiness, 3) speed, 4) creation, and 5) accomplishing task without teacher’s help. At the first cycle, 27.77% were able to replicate the determined pattern. In the same way, 34.72% students were able to perform the task tidily. Regarding to speed aspect, 27.77% managed to finish the task fast. 38.88% students showed creativity in replicating various shapes, and 29.16% managed to accomplish the task independently. In brief, the percentage of success at Cycle 1 reached 63,31%, which means, the students were developed as expected. Furthermore, at Cycle 2, students experienced progress in each aspect. 44.44% students were able to reproduce shape which had been determined. 43% students managed to show the aspect of tidiness in replication. 37.49% managed to do the task fast. 37.49% students affirmed creativity in creating various shapes, and 37.49% were able to replicate the shapes without help from the teacher. Concisely, in Cycle 2, students’ ability in replicating shapes increased and reached 81%. It can be said that the students were developed very well in terms of replicating shapes.In conclusion, gradation learning strategy is effective for improving students’ ability in replicating shapes. Therefore, it is suggested for teachers to use this strategy later on.